ON THE CONTROL OF THE HEAT CONDUCTION - Fayziev, Yusuf Ergashivich (IIUM Engineering Journal, 2018)
Mathematical models of thermo control processes in a rectangular plate are considered. In the model under consideration, the temperature inside a plate is controlled by heat exchange through one boundary while the other three are insulated. The control parameter is a function that satisfies certain integral equations. Sufficient conditions for achieving the given projection of the temperature at a fixed point on the plate and given average temperature are studied. ABSTRAK: Model matematik bagi proses kawalan suhu dalam bekas segi empat tepat telah dipilih. Melalui model ini, suhu bekas dikawal dengan menukar haba melalui salah satu sisi bekas, manakala tiga sisi lain telah ditebat. Parameter kawalan ini ialah fungsi, di mana ia sesuai dengan persamaan sesetengah integral. Keadaan sesuai bagi mencapai suhu tetap bekas seperti cadangan dan suhu purata yang diberikan turut dikaji.